MENINGKATKAN KEMAMPUAN ANAK USIA DINI DALAM MENGENAL HURUF MELALUI PERMAINAN KOTAK ALFABET - Salam, Abdul; Larau, Sri Amini Fadhila; Husen (Pusat Studi Gender dan Anak, IAIN Palu, 2024)
The research problem was whether the abilitiy to recognize children in group A could increase after using the alphabet box game in East Longkoga ABA Kindergarten. The research subjects consisted of 10 students, with four boys and six girls. The research was conducted in two cycles, each consisting of two meetings. Learning activities consist of four stages, namely the planning stage, the implementation stage, the observation, and the reflection stage. Data collection techniques used in this study are observation and documentation sheets. Data analysis was carried out in a comparative descriptive manner, namely comparing the values between cycles processed using the percentage calculation (%) according to the formula. The research results show that on the indicator of the ability to recognize the alphabet at the pre-cycle stage, there were six students, or 60% who reached the Beginning to Develop category. At the end of the cycle I, six students or 60%, reached the Expected Developing category. At the end cycle II, nine students or 90% reached the Very Good Development category. Furthermore, two students or 20%, reached the Beginning to Develop category in the indicator of the ability to pronounce alphabetic forms in the pre-cycle stage. At the end of the cycle I, four students or 40%, started to reach the Expected Developing category. At the end of cycle II, nine students or 90%, were in the Very Good Developing category. Finally, indicators of the ability to pronounce the alphabet at the pre-cycle stage have four students or 40%, in the Beginning to Develop category. At the end of the cycle I, two students or 20%, had reached the Expected Developing category, and one students or 10%, had reached the Very Good Developing category. And at the end of cycle II, nine students or 90% , were already in the Very Good Developing category. Based on the research above, alphabet box games can improve the ability to recognize letters in group A children in East Longkoga ABA Kindergarten.